Exploring the principals’ attitudes toward the impact of in-service teacher training in India - Joshi, K.M.; Ahir, Kinjal V.; Upadhyay, Govinda Raj; Priya, Ashutosh; Bhatta, Dharma Dev (AMC Journal (Dhangadhi), 2026)
This study examines secondary school principals’ attitudes toward in-service teacher training and compares these attitudes across gender, age, and professional experience in India. Using a cross-sectional survey design, data were collected through a structured Likert-scale questionnaire administered to public and private school principals. Descriptive statistics, independent sample t-tests, and one-way ANOVA were employed for analysis. The findings indicate an overall above-average positive attitude toward in-service teacher training, with no statistically significant differences across gender, age groups, or years of experience. By incorporating principals’ perspectives an area previously underexplored this study provides practical insights to inform the planning and improvement of in-service teacher training programs aimed at enhancing educational quality.